Faith, hope, and Ivy June - Naylor, Phyllis Reynolds (Delacorte Press : Scholastic Inc., 2009)
During a student exchange program, seventh-graders Ivy June and Catherine share their lives, homes, and communities, and find that although their lifestyles are total opposites they have a lot in common.